Do you have anymore information that doesn’t help that much
Answer:
a) 2x+3
b) 5x-7
c) 2x-10
d) 3x/2
Step-by-step explanation:
the number considered is x
we do 2x-1/y=w+2/2z
2x-1/y we multiple each side y
2x-1/y×y=2x-1
then w+2/2z
we said×2z×2z
then we got
w+2
later
2x-1=w+2=
then 1 become another side
which is 1+2=3
then
w=3-2x
I hope it's correct
1/5 divided by 6
6 = 6/1
When dividing fractions, we follow a rule called "Keep, change, flip."
It then becomes: 1/5 * 1/6 = 1/30
1 fifth divided by 6 equals 1/30
Answer:
(4t − 3) (t − 6)
Step-by-step explanation:
Using AC method:
Given a quadratic ax² + bx + c, find factors of ac that add up to b. Divide those factors by a and reduce. The denominators become the coefficients and the numerators become the constants.
Here, a = 4, b = -27, and c = 18.
ac = 4 × 18 = 72
Factors of 72 that add up to -27: -3 and -24
Divide factors by a: -3/4 and -24/4
Reduce: -3/4 and -6/1
So the factored expression is:
(4t − 3) (t − 6)